2023
DOI: 10.1088/2399-6528/acd986
|View full text |Cite
|
Sign up to set email alerts
|

A new derivation of the Minkowski metric

Abstract: The four dimensional spacetime continuum, as first conceived by Minkowski, has become the dominant framework within which to describe physical laws. 
In this paper, we show how this four-dimensional structure is a natural property of physical three-dimensional space, if modeled with Clifford geometric algebra $ C\ell(\Re^3) $. We find that Minkowski spacetime can be embedded within a larger eight dimensional structure. This then allows a generalisation of the invariant interval and the Lorentz transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Researchers have also taken a more mathematical approach to exploring the depths of the Minkowski metric. For instance, in Chappell et al (2023) [11], the authors presented a new derivation to the Minkowski metric. They demonstrated that the Minkowski metric could be obtained as an emergent property from physical space modeled as a Clifford algebra, Cl R 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also taken a more mathematical approach to exploring the depths of the Minkowski metric. For instance, in Chappell et al (2023) [11], the authors presented a new derivation to the Minkowski metric. They demonstrated that the Minkowski metric could be obtained as an emergent property from physical space modeled as a Clifford algebra, Cl R 3 .…”
Section: Introductionmentioning
confidence: 99%